Legitimacy in WTO law and investment arbitration: the role of the contracting parties - Herfried Wöss (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
International investment protection standards are the result of a "dilatory formula compromise," i.e. a formal compromise without agreement on its precise content, due to historical reasons. Their development is mainly through arbitral awards and scholarly writings in the absence of the further involvement of the contracting parties, which raises legitimacy issues.
Keywords: 330